Reduced microbial stability in the active layer is associated with carbon loss under alpine permafrost degradation - Wu, Ming-Hui; Chen, Sheng-Yun; Chen, Jian-Wei; Xue, Kai; Chen, Shi-Long; Wang, Xiao-Ming; Chen, Tuo; Kang, Shi-Chang; Rui, Jun-Peng; Thies, Janice E; Bardgett, Richard D; Wang, Yan-Fen (Proceedings of the National Academy of Sciences - PNAS, 2021)
Permafrost degradation may induce soil carbon (C) loss, critical for global C cycling, and be mediated by microbes. Despite larger C stored within the active layer of permafrost regions, which are more affected by warming, and the critical roles of Qinghai-Tibet Plateau in C cycling, most previous studies focused on the permafrost layer and in high-latitude areas. We demonstrate in situ that permafrost degradation alters the diversity and potentially decreases the stability of active layer microbial communities. These changes are associated with soil C loss and potentially a positive C feedback. This study provides insights into microbial-mediated mechanisms responsible for C loss within the active layer in degraded permafrost, aiding in the modeling of C emission under future scenarios.